شخصية المرأة في روايتي "عذراء جاكرتا" لنجيب الكيلاني و"آيات الحب" لحبيب الرحمن الشيرازي: دراسة مقارنة - رمضان، إلهام (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study examines the female characters in Jakarta's Virgin (1972) by Najib Al-Kilani and Verses of Love (2004) by Habiburrahman El Shirazy of Indonesia from the perspective of literary criticism and Islamic literature. This research analyses the dimensions of the female characters and the writers' methods of characterization as well as the Islamic values in both novels. This comparative study investigates the themes and conflicts in both novels to examine the dimensions of the female characters and the methods of characterization in terms of language, environment and culture. The researcher found that there are similarities and differences between the themes and conflicts related to the women in both novels. In sum, these two novels are Islamic novels which feature different characteristic of women involved in conflicts. The first novel showed a woman as the main character who resists communism in Indonesia, while, the second novel has a pious man as the main character facing challenges in his relationships with women from Egypt, Turkey and Indonesia. Finally, the researcher concludes that both novelists have successfully depicted various female characters and this proves that both novelists are innovative.